Flavonoids with Glutathione Antioxidant Synergy: Influence of Free Radicals Inflow - Igor Ilyasov; Vladimir Beloborodov; Daniil Antonov; Anna Dubrovskaya; Roman Terekhov; Anastasiya Zhevlakova; Asiya Saydasheva; Vladimir Evteev; Irina Selivanova (MDPI AG, 2020)
This report explores the antioxidant interaction of combinations of flavonoid-glutathione with different ratios. Two different 2,2'-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid radical (ABTS•+)-based approaches were applied for the elucidation of the antioxidant capacity of the combinations. Despite using the same radical, the two approaches employ different free radical inflow systems: An instant, great excess of radicals in the end-point decolorization assay, and a steady inflow of radicals in the lag-time assay. As expected, the flavonoid-glutathione pairs showed contrasting results in these two approaches. All the examined combinations showed additive or light subadditive antioxidant capacity effects in the decolorization assay. This effect showed slight dilution dependence and did not change when the initial ABTS•+ concentration was two times as high or low. However, in the lag-time assay, different types of interaction were detected, from subadditivity to considerable synergy. Taxifolin-glutathione combinations demonstrated the greatest synergy, at up to 112%; quercetin and rutin, in combination with glutathione, revealed moderate synergy in the 30-70% range; while morin-glutathione appeared to be additive or subadditive. In general, this study demonstrated that, on the one hand, the effect of flavonoid-glutathione combinations depends both on the flavonoid structure and molar ratio; on the other hand, the manifestation of the synergy of the combination strongly depends on the mode of inflow of the free radicals.